Formation mechanism and process optimization of nano Al2O3-ZrO2 eutectic ceramic via laser engineered net shaping (LENS). Issue 17 (1st December 2017) - Yan, Shuai; Wu, Dongjiang; Ma, Guangyi; Niu, Fangyong; Kang, Renke; Guo, Dongming
Abstract: Periodic banded structure has great influence on the microstructure and fracture toughness of eutectic ceramic produced by LENS system. Formation Mechanism of periodic banded structure and influence regularity from laser power, scanning speed, feeding rate and feeding proportion were studied. X-ray diffractometer analysis and scanning electron microscopy observation were carried out for sample phase composition and microstructure respectively. Microhardness was measured by vivtorinox hardness tester, and surface fracture toughness was calculated by indentation crack length. The results show that periodic banded structure is divided into organizational coarsening zone and divorced eutectic zone. Due to the influence of upper cladding layer heat, the eutectic structure in the interlayer bonding zone is obviously coarsening in organization coarsening zone. When laser power is lower, Al2 O3 phase takes the lead in nucleation and grows up quickly, forming a discrete block structure of Al2 O3 particles in divorced eutectic area. When laser power is higher, ZrO2 phase takes the lead in nucleation and forms a discrete block structure of ZrO2 particles. Al2 O3 -ZrO2 ceramics with the shape of thin-walled and cylinder were manufactured under the optimized process conditions, whose independent nucleation disappears and the thickness of periodic banded structure reduces to 10 µm. The eutectic spacing of prototype structure reaches 120–130 nm, has uniform microstructure and good surface morphology. The average micro-hardness is 18.59 GPa. Surface fracture toughness increases to 6.52 MPa m 1/2 .